Gathering insights into volcanic risk from Auckland to the Andes, Antilles, and Arabia: an unexpected journey to professorship in volcanology - Lindsay, Jan M. (Frontiers in Earth Science, 2024)
In 2020 I was promoted to Professor at Waipapa Taumata Rau the University of Auckland (UoA), joining the small circle (now three) of women who had achieved promotion to Professor in Geology in Aotearoa New Zealand 1 , and the first ever in the field of volcanology. This promotion was a gratifying and somewhat unexpected achievement for me considering that I had started out studying languages and linguistics! In this contribution, which is based on my "inaugural" lecture as Professor in 2021, I provide an overview of my journey, framed primarily through the work of my doctoral students. I pay particular focus on the Andes where I worked on large silicic caldera systems, the Lesser Antilles, characterised by andesite and dacitic dome complexes and stratovolcanoes, and the distributed basaltic volcanism in Auckland and Saudia Arabia. I share some insights gained along the way and describe how these have influenced a shift in my research from more fundamental petrology to more applied volcanology over the course of my career.